Peranan Metode Desain Eksperimen dalam Formulasi Sediaan Farmasi - Triandri Permana; Fitrianti Darusman (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. To develop high-quality pharmaceutical products, traditional approaches based on univariate or trial-and-error methods that cause some problems such as non-reproducible methods, high costs, and time-consuming. To overcome this drawback, a new concept of experimental design has been applied. Experimental design is a statistical method that is widely used in the pharmaceutical industry in the implementation of quality by design. This method is used to establish quantitative relationships between potential critical parameters (related to the product, process, method) and the determined response (e.g. product quality). Based on the description, the formulation of the problem in this study is what experimental design methods can be used in the development and formulation of pharmaceutical preparations?. This research was conducted using Journal review method with literature study. Collection techniques with various scientific literature both primary and secondary. In the announcement of data and Journal searches used online-based searches such as Pubmed, Science Direct, and Google Scholar. The results of this study are factorial design, complete factorial design, fractional factorial design, Plackett-burman design, central composite design, box-Behnken designs, and mixed design are experimental designs that can be used in the development and formulation of pharmaceutical preparations. Abstrak. Untuk mengembangkan produk farmasi yang berkualitas tinggi, pendekatan tradisional berdasarkan metode univariat atau coba-coba menyebabkan beberapa masalah seperti metode yang tidak reprodusibel, biaya yang tinggi, dan memakan waktu. Untuk mengatasi kelemahan ini, konsep baru yaitu desain eksperimen telah diterapkan. Desain eksperimen merupakan metode statistik yang digunakan secara luas di industri farmasi dalam implementasi quality by besign. Metode ini digunakan untuk membangun hubungan kuantitatif antara parameter kritis potensial (terkait dengan produk, proses, metode) dan respons yang ditentukan (misalnya kualitas produk). Berdasarkan uraian tersebut maka rumusan masalah dalam penelitian ini yaitu metode desain eksperimen apa saja yang dapat digunakan dalam pengembangan dan formulasi sediaan farmasi?. Penelitian ini dilakukan menggunakan metode review jurnal dengan studi pustaka. Teknik pengumpulan dengan berbagai literatur ilmiah baik primer maupun sekunder. Pada pengumulan data dan pencarian jurnal digunakan pencarian berbasis online seperti Pubmed, Science Direct, dan Google Scholar. Hasil dari penelitian ini yaitu desain faktorial, desain faktorial lengkap, desain faktorial fraksional, desain Plackett-burman, central composite design, box-Behnken designs, dan desain campuran merupakan desain eksperimen yang dapat digunakan dalam pengembangan dan formulasi sediaan farmasi.